PENGARUH PEMBERIAN Trichoderma asperellum TZ11DI1 TERHADAP PENYAKIT LAYU FUSARIUM (Fusarium sp.) DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Nurdila Talib; Rida Iswati; Siska Irhamnawati Pulogu (Percetakan Umi Toaha Makassar, 2026)
This study aims to determine the administration of Trichoderma asperellum TZ11DI1 against Fusarium wilt disease in shallot plants. This study was conducted at the Laboratory of the Agricultural Plant Protection Agency of Gorontalo Province and agricultural land in Hulawa Village, Telaga District, Gorontalo Regency, from February to May 2025. This study used a Completely Randomized Design (CRD) with negative control treatments (T0), Positive control of chemical pesticide application (T1), application of Trichoderma Asperellum TZ11DI1 5 grams (T3), application of Trichoderma Asperellum TZ11DI1 10 grams (T2), and application of Trichoderma Asperellum TZ11DI1 15 grams (T3) each repeated 8 times, so that 40 experimental units were obtained. The variables observed were the incubation period, disease incidence, attack intensity, number of bulbs, and bulb weight. Data analysis used ANOVA and a further LSD test at a significance level of 5%. The results showed that T. asperellum TZ11DI1 treatment was effective in extending the incubation period, reducing disease incidence, and reducing the intensity of Fusarium wilt disease attacks on shallot plants. A higher dose of T. asperellum TZ11DI1 15 grams) significantly reduced the attack rate and produced an average bulb weight of 56.46 g, and the number of bulbs was 18.25 per clump.